2018
DOI: 10.1080/09853111.2018.1458935
|View full text |Cite
|
Sign up to set email alerts
|

Geomorphological signatures of the evolution of active normal faults along the Langshan Mountains, North China

Abstract: chengdu, china; d china earthquake networks center, china earthquake administration, Beijing, china

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
17
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 97 publications
(124 reference statements)
0
17
0
1
Order By: Relevance
“…At present, faults in plain areas can be identified by LiDAR-derived high-resolution digital elevation models (DEM) (Kondo et al 2008;Bhosle et al 2009;Ahmad et al 2015;Deffontaines et al 2017;Goto et al 2017;Chang et al 2018;Dong and Chen 2018). Various geomorphological indexes have been proposed to quantify fault activity (Troiani and Seta 2008;Arrowsmith and Zielke 2009;Parul et al 2013;Troiani et al 2014;Gao et al 2015;Liu et al 2015;Liu and Du 2016;Kaushal et al 2017;Wang et al 2017;He et al 2018;Pavano et al 2018;Sharma et al 2018;Wang et al 2019). Terrain analysis of seismogenic faults has been well documented in studies areas around the world (Cello et al 2000;Lin et al 2003;Pucci et al 2003;Maschio et al 2005;Irikura 2012; Mahmood and Gloaguen 2012 ;Robinson and Davies 2013 ;Koukouvelas et al 2018), and has become a major method for studying neotectonics, seismogeology, and paleoseismology (Papanikolaou et al 2015).…”
Section: Introductionmentioning
confidence: 99%
“…At present, faults in plain areas can be identified by LiDAR-derived high-resolution digital elevation models (DEM) (Kondo et al 2008;Bhosle et al 2009;Ahmad et al 2015;Deffontaines et al 2017;Goto et al 2017;Chang et al 2018;Dong and Chen 2018). Various geomorphological indexes have been proposed to quantify fault activity (Troiani and Seta 2008;Arrowsmith and Zielke 2009;Parul et al 2013;Troiani et al 2014;Gao et al 2015;Liu et al 2015;Liu and Du 2016;Kaushal et al 2017;Wang et al 2017;He et al 2018;Pavano et al 2018;Sharma et al 2018;Wang et al 2019). Terrain analysis of seismogenic faults has been well documented in studies areas around the world (Cello et al 2000;Lin et al 2003;Pucci et al 2003;Maschio et al 2005;Irikura 2012; Mahmood and Gloaguen 2012 ;Robinson and Davies 2013 ;Koukouvelas et al 2018), and has become a major method for studying neotectonics, seismogeology, and paleoseismology (Papanikolaou et al 2015).…”
Section: Introductionmentioning
confidence: 99%
“…2018), the Langshan mountains in northern China (He et al . 2018), and the Zagros mountains in northern Iraq (Obaid & Allen 2017; Obaid & Allen 2019; Zebari et al . 2019).…”
mentioning
confidence: 99%
“…An analysis by He et al . (2018) in northern China revealed that the quantitative geomorphologic indices could explain the disequilibrium landscape responding to active rock uplift and channel incision.…”
mentioning
confidence: 99%
See 2 more Smart Citations